Conflict in Resource Management: A Comparative Study of Mobilization of Marginalized Groups - L. Bracamonte, Nimfa; Bradford, David; Khaushik, Anumpa; Mariño, Eduardo; Mbikusita-Lewanika, Inonge; Parker, Juliana (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
"Conflict in Resource Management: A Comparative Study of Mobilization of Marginalized Groups" attempts to investigate the dynamics of resource management and mobilization of marginalized groups. Employing the comparative method, 5 case studies of marginalized groups represent 3 continents such as Africa (Sierra Leone and Zambia), Asia (India and Philippines), and Latin America (Nicaragua). The study shows that internal conflict may emanate from incompatibilities over management of resources and create cleavages between the deprived and disadvantage groups and the state itself. In economic modernization, whenever some sectors do not benefit from what is considered "development," they resort to mobilization to redress their grievances. In this respect, collective action is enhanced through the community, organization, and governmen-lal factors. The community factor which gives the marginalized groups a sense of identity and collective interests appears to be the convergence of the S cases The study further manifests the discrepancy between the nature of resource management and level of mobilization which may be attributable to the particularies specificities of the country. For instance, the political atmosphere or efforts of the government towards effective resource management matters. Proper resource management embodies the factors of empowerment, sustainability, transparency, and equity in the distribution of scarce resources.